Some biological, behavioral and social aspects of the perfumery use in the Ukrainian population sample (part 1. age associations) - Filiptsova, Olga; Bashura, Olexander; Naboka, Olga; Kran, Oleksandra; Almakaiev, Maksym; Kukhtenko, Halyna; Martyniuk, Tetiana; Osypenko, Yuliia (ScienceRise: Biological Science, 2022)
The aim. The study encompassed some aspects related to perfumes use, which can potentially influence the individual perfume choice, in particular, among different age groups of the Ukrainian population. Factors related to perfumes choice, the state of awareness of respondents regarding quality, safety, and existing stereotypes regarding the characteristics of perfumes and potential harmful effects on the human body were investigated. Materials and methods. The analysis was performed on a sample of 124 residents of Ukraine. Respondents, who were randomly selected, were offered a questionnaire, developed by us, which included 15 items on the demographic characteristics of the subjects and questions related to the perfume use of and stereotypes about them. The Pearson chi-squared (χ2) test was used to analyze the relationships between qualitative characteristics. Results and discussion. About 98 % of surveyed persons in Ukraine use perfumery. Associations were found between age and the probability of purchase by the study participants of non-original perfume products and awareness of the safety of various perfume products. It has been established, that the determining factors when choosing a perfume is a certain scent, while the brand is given secondary importance. An increase in the effect of the brand in older age groups of the population has been demonstrated. Behavioral features of perfume use have been established: in younger women, it is associated with increased self-esteem and the influence of social networks, with age, the focus shifts to the desire for a positive effect on the mood from the use of a certain fragrance. However, in all age groups, the main purpose of perfume using was to improve the emotional state. Middle-aged women are more democratic in choosing perfumery with a specific gender orientation. Conclusions. For the first time in Ukraine, a pilot study was conducted to find possible associations between some biological, behavioral and demographic characteristics and the perfume use. Such factors as age and education level are promising for further analysis of the selected issues